Pharmacological evidences for the blood pressure lowering and cardiovascular inhibitory actions of the essential oil of Thymus serrulatus hochst. Ex benth - Rehman, Najeeb Ur; Ansari, Mohd Nazam; Aldossari, Abdulrahman A.; Alhatlan, Thamer A.; Palla, Amber Hanif; Karim, Aman; Noman, Muhammad (Frontiers in Pharmacology, 2026)
BackgroundT. serrulatus is used in folk medicine for the treatment of cardiovascular disorders, including hypertension. This study investigates its hypotensive, cardiac-depressant, and vasodilatory activities.MethodsThe hypotensive effect of Thymus serrulatus essential oil was evaluated in vivo in anesthetized rats by measuring changes in mean arterial blood pressure following intravenous administration. Ex vivo, cardiac-depressant activity was assessed in isolated guinea-pig atrial preparations, and vasodilatory effects were examined in rat aortic rings.ResultsIntravenous administration of T. serrulatus essential oil produced a dose-dependent (1–10 mg/kg) reduction in arterial blood pressure. In spontaneously beating guinea-pig atrial tissues, the oil exerted negative chronotropic and inotropic effects at concentrations of 0.1–5 mg/mL. In rat aorta, it caused complete relaxation of phenylephrine (PE, 1 μM)-induced contractions, with an EC50 of 1.27 mg/mL, while partial relaxation (59% ± 3%) was observed against high K+ (80 mM). The vasodilatory effect against PE was not significantly altered by endothelium removal or atropine pretreatment, indicating an endothelium- and muscarinic-independent mechanism. Preincubation with a lower concentration (0.1 mg/mL) produced a rightward shift in PE-mediated concentration–response curves (CRCs) without reducing maximal response, similar to prazosin-like competitive antagonism. A higher concentration (0.3 mg/mL) suppressed the maximal PE response, consistent with non-competitive antagonism comparable to verapamil. In Ca++-free medium, preincubation with T. serrulatus (0.3 and 1 mg/mL) shifted Ca2+ CRCs to the right with reduced maximal response, further supporting Ca++ channel–blocking activity.ConclusionT. serrulatus essential oil exhibits hypotensive, cardiac-depressant, and vasodilatory effects, likely mediated through α-adrenergic antagonism and Ca++ channel blockade. These findings provide pharmacological support for its traditional use in cardiovascular disorders, including hypertension.